int(cos^4(x)sin^2(x))dx=int((1+cos(2x))/2)^2((1-cos(2x))/2)dx
Using formula
cos^2(x)=(1+cos(2x))/2
sin^2(2x)=(1-cos(2x))/2
int((1+cos(2x))/2)^2((1-cos(2x))/2)dx
=int((1+cos^2(2x)+2cos(2x))(1-cos(2x)))/8dx
=int((1+cos^2(2x)+2cos(2x)-cos(2x)-cos^3(2x)-2cos^2(2x))/8)dx
int( 1+cos(2x)-cos^2(2x)-cos^3(2x))/8dx
1/8( int (dx)+int cos(2x) dx-int(cos^2(2x)dx-int(cos^3(dx)
int cos^2(2x) dx=int(1+cos(4x))/2dx=x/2+sin(4x)/8
intcos^3(2x)dx=int(1-sin^2(2x))cos(2x)dx
=int cos(2x)-sin^2(2x)cos(2x)dx=sin(2x)/2-sin^3(2x)/6
1/8( int (dx)+int cos(2x) dx-int(cos^2(2x)dx-int(cos^3(dx)
=1/8(x+sin(2x)/2-x/2-sin(4x)/8-sin(2x)/2+sin^3(2x)/6)
=1/16(x-sin(4x)/4+sin^3(2x)/3)